Shortened derivatives from native antimicrobial peptide LyeTx I: In vitro and in vivo biological activity assessment. Issue 4 (February 2021) - Fuscaldi, Leonardo Lima; de Avelar Júnior, Joaquim Teixeira; dos Santos, Daniel Moreira; Boff, Daiane; de Oliveira, Vívian Louise Soares; Gomes, Karla Aparecida Guimarães Gusmão; Cruz, Rosana de Carvalho; de Oliveira, Patrícia Luciana; Magalhães, Paula Prazeres; Cisalpino, Patricia Silva; Farias, Luiz de Macêdo; de Souza-Fagundes, Elaine Maria; et al.
In the continuing search for novel antibiotics, antimicrobial peptides are promising molecules, due to different mechanisms of action compared to classic antibiotics and to their selectivity for interaction with microorganism cells rather than with mammalian cells. Previously, our research group has isolated the antimicrobial peptide LyeTx I from the venom of the spider Lycosa erythrognatha . Here, we proposed to synthesize three novel shortened derivatives from LyeTx I (LyeTx I mn; LyeTx I mnΔK; LyeTx I mnΔKAc) and to evaluate their toxicity and biological activity as potential antimicrobial agents. Peptides were synthetized by Fmoc strategy and circular dichroism analysis was performed, showing that the three novel shortened derivatives may present membranolytic activity, like the original LyeTx I, once they folded as an alpha helix in 2.2.2-trifluorethanol and sodium dodecyl sulfate. In vitro assays revealed that the shortened derivative LyeTx I mnΔK presents the best score between antimicrobial (↓ MIC) and hemolytic (↑ EC50 ) activities among the synthetized shortened derivatives, and LUHMES cell-based NeuriTox test showed that it is less neurotoxic than the original LyeTx I (EC50 [LyeTx I mnΔK] ⋙ EC50 [LyeTx I]). In vivo data, obtained in a mouse model of septic arthritis induced by Staphylococcus aureus, showed that LyeTx I mnΔK is able to reduce infection, as demonstrated by bacterial recovery assay (∼10-fold reduction) and scintigraphic imaging (less technetium-99m labeled-Ceftizoxime uptake by infectious site). Infection reduction led to inflammatory process and pain decreases, as shown by immune cells recruitment reduction and threshold nociception increment, when compared to positive control group. Therefore, among the three shortened peptide derivatives, LyeTx I mnΔK is the best candidate as antimicrobial agent, due to its smaller amino acid sequence and toxicity, and its greater biological activity.